PELAPISAN MAGNETIT DENGAN SILIKA BERSUMBER ABU SEKAM PADI - , ARIEF HAMDANY S, Prof. Nuryono, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research on coating of magnetite (Fe3O4) with silica using a solution of sodium silicate (Na2SiO3) derived from rice husk ash has been carried out. This research was conducted to determine a method synthesis of magnetite giving high crystalline and to study the effect of silica coating on magnetite properties. Magnetite was synthesized by method of coprecipitation with solvent and free-solvent at the mol ratio of Fe2+: Fe3+ 2:1. The influence of nitrogen, type of agent precipitation was used, and the heating temperature on crystallinity of magnetite was examined. Coatings was conducted by sol-gel process